Co‐Assembly of LDH Nanosheets with Crown Ethers: Structural Transformation and Water‐Adsorption Behavior. Issue 8 (17th January 2013) - Ma, Shulan; Wang, Juan; Du, Li; Fan, Cuihong; Sun, Yahong; Sun, Genban; Yang, Xiaojing
Abstract: Co‐assembly of inorganic LDH nanosheets with an organic azacrown ether carboxylic acid derivative was studied by a flocculation method. The homogeneous structure seen in the wet state changed markedly after drying: a staging structure transformed into a homogeneous one after increased assembly times. The experimental observations, changeover from homogeneous to staging and unequal charges of organic and inorganic guests in gallery, might suggest the Daumas–Hérold model applicable in LDH system. The composites with staging could function as powerful water adsorption materials with facile reversibility. Abstract : Co‐assembly of LDH nanosheets with organic crown ether/inorganic anions results in structural transformation that suggests flexibility of the LDH layers and the Daumas–Hérold model. A water adsorption study reveals composites with staging structures that can be used as water adsorption materials with good reusability.